Effect of pre-treatment palm oil mill effluent POME on biohydrogen production by local isolate clostridium butyricum - Ahmad Kamal, Syafawati; Mansor, Mariatul Fadzillah; Md. Jahim, Jamaliah; Anuar, Nurina (2011)
Palm oil mill effluent (POME) contains approximately 6% fiber. The effectiveness of pre-treatment on POME can serve a very good feedstock for hydrogen production in fermentation process. In this research, the effectiveness of pre-treatment methods on POME treated using acid and base were analysed based total carbohydrate and reducing sugar content. By using 1M NaOH with heat treatment, 26.12% carbon source converted to reducing sugar while by using 1M H2SO4 with heat treatment, over 32.09% carbon source converted to reducing sugar. The highest increment of total carbohydrate where from acid-heat treatment with 26.1% increment from initial concentration. At the initial pH (5.5) with fermentation temperature 37 oC, the highest hydrogen production rate given by acid-heat treatment was 0.5mL H2/mL POME. Different for initial pH 7.0 with the same temperature, the highest hydrogen produced rate was given by base-heat treatment with 0.59 mL H2/mL POME. The production of hydrogen in 2L bioreactor given much higher hydrogen production compare to production in serum bottle. This fermentation was run in batch mode with initial pH 7 and control at 5.5. The maximum hydrogen produce was 4304 mL H2/ L POME from acid-heat treatment.